A GIS modelling framework to evaluate marine spatial planning scenarios: Co-location of offshore wind farms and aquaculture in the German EEZ. (May 2015) - Gimpel, Antje; Stelzenmüller, Vanessa; Grote, Britta; Buck, Bela H.; Floeter, Jens; Núñez-Riboni, Ismael; Pogoda, Bernadette; Temming, Axel
Abstract: The concept of co-location of marine areas receives an increased significance in the light of sustainable development in the already heavily used offshore marine realm. Within this study, different spatial co-location scenarios for the coupling of offshore aquacultures and wind farms are evaluated in order to support efficient and sustainable marine spatial management strategies. A Geographic Information System (GIS) and multi-criteria evaluation (MCE) techniques were combined to index suitable co-sites in the German exclusive economic zone of the North Sea. The MCE was based on criteria such as temperature, salinity or oxygen. In total, 13 possible aquaculture candidates (seaweed, bivalves, fish and crustaceans) were selected for the scenario configuration. The GIS modelling framework proved to be powerful in defining potential co-location sites. The aquaculture candidate oarweed ( Laminaria digitata ) revealed the highest suitability scores at 10–20 m depth from April to June, followed by haddock ( Melanogrammus aeglefinus ) at 20–30 m depth and dulse ( Palmaria palmata ) and Sea belt ( Saccharina latissima ) at 0–10 m depth between April and June. In summary, results showed several wind farms were de facto suitable sites for aquaculture since they exhibited high suitability scores for Integrated Multi-Trophic Aquaculture (IMTA) systems combining fish species, bivalves and seaweeds. The present results illustrate how synergies may be realised between competing needs of both offshore wind energy and offshore IMTA in the German EEZ of the North Sea. This might offer guidance to stakeholders and assist decision-makers in determining the most suitable sites for pilot projects using IMTA techniques. Highlights: Spatial co-location scenarios for the coupling of offshore aquacultures and wind farms are evaluated. Geographic information system (GIS) and multi-criteria evaluation (MCE) techniques were combined. Possible aquaculture candidates (seaweed, bivalves, fish and crustaceans) were selected. L. digitata, M. aeglefinus and O. edulis revealed the highest suitability scores from April to June. Several wind farms provide de facto suitable sites for aquaculture and exhibit high suitability scores for IMTA systems combining fish species, bivalves and seaweeds.